2017
DOI: 10.1016/j.jphotobiol.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inactivation of conidia of the fungus Colletotrichum abscissum on Citrus sinensis plants with methylene blue under solar radiation

Abstract: Antimicrobial photodynamic treatment (APDT) is a promising light based approach to control diseases caused by plant-pathogenic fungi. In the present study, we evaluated the effects of APDT with the phenothiazinium photosensitizer methylene blue (MB) under solar radiation on the germination and viability of conidia of the pathogenic fungus Colletotricum abscissum (former Colletotrichum acutatum sensu lato). Experiments were performed both on petals and leaves of sweet orange (Citrus sinensis) in different seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 55 publications
0
25
0
9
Order By: Relevance
“…Previous aPDT studies already showed that MB was an efficient PS in the inactivation of various microorganisms, namely other Gram-positive bacteria such as Staphylococcus aureus, Gram-negative bacteria such as Pseudomonas aeruginosa [32] and Vibrio parahaemolyticus [33], and fungi such as Colletotricum abscissum [34] and Candida albicans [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous aPDT studies already showed that MB was an efficient PS in the inactivation of various microorganisms, namely other Gram-positive bacteria such as Staphylococcus aureus, Gram-negative bacteria such as Pseudomonas aeruginosa [32] and Vibrio parahaemolyticus [33], and fungi such as Colletotricum abscissum [34] and Candida albicans [35].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that natural photosensitizers such as coumarins and furocoumarins or synthetic ones such as phenothiazinium and porphyrins inactivated pathogenic agents as virus (Tobacco mosaic virus), bacteria ( Pseudomonas syringae ) and fungi ( Collectotrchum abscissum, Colletotrichum gloeosporioides, Collectotrichum acutatum, Aspergillus nidulans, Fusarium oxysporum, Fusarium moniliforme, Fusarium solani ) (Table 1 ). However, when spotted on orange tree and strawberry plants, or on kiwi contaminated leaves under solar radiation, the leaves and flowers were not affected by either natural/synthetic photosensitizers excepted for strawberry leaves that were damaged upon treatment with 100 μM phenothiazinium (Orlob, 1967 ; de Menezes et al, 2014a , b ; Fracarolli et al, 2016 ; Gonzales et al, 2017 ; Jesus et al, 2018 ). In another extended context, Issawi and co-workers conceived a double target strategy that could eradicate in the same time unwanted vegetation and plant pathogens without killing plants of agronomic interest (Figure 1B ).…”
Section: Direct Photodynamic Stress: An Old Story With Novel Developmmentioning
confidence: 99%
“…Gilberto U. L. Braga explained that antimicrobial photodynamic treatment (APDT) is a promising alternative to conventional antifungal agents that can be used to kill fungi, which cause diseases in animals or plants (de Menezes et al, 2014;Gonzales et al, 2017). APDT, using phenothiazinium photosensitizers, efficiently kills planktonic cells of Candida species and conidia of several pathogenic fungi, damages the fungal plasma membrane increasing its permeability and greatly impacting their proteomes (Brancini et al, 2016).…”
Section: Fungal Photobiology In the Context Of Stressmentioning
confidence: 99%